Chaetoceros decipiens Cleve 1873 ... - Li, Yang; Boonprakob, Atchaneey; Gaonkar, Chetan C.; Kooistra, Wiebe H. C. F.; Lange, Carina B.; Hernández-Becerril, David; Chen, Zuoyi; Moestrup, Øjvind; Lundholm, Nina (Zenodo, 2017)
Chaetoceros decipiens Cleve 1873, p. 11, Pl. I, fig 5a & 5b, emend. Li, Boonprakob, Moestrup & Lundholm Figs 1– 3, 20E and 20F and S 1 and S 2 Figs. Synonym: Chaetoceros grunowii Schütt 1895 Lectotype designated here. A holotype was not chosen by Cleve. We have chosen slide MIC 5366 in P. T. Cleve’s collection, Stockholm, Sweden as the lectotype. The slide is labelled “Atlanten ytan 27/5-71 Lat 60˚25 Long 19˚50 ThM Fries”. Figs 1A, 1B and 2A illustrate the lectotype. Examination of the type material revealed the morphology to be in agreement with Cleve’s description and with our strains identified as C. decipiens. The Cleve material from the North Atlantic and the Davis Strait looked similar. Most prominently some sibling setae were found to fuse for a longer distance; however, in others no fusion was seen. A very delicate striation of the setae was observed, in agreement with Cleve [7]. We did not at first observe the striation in our cultured material, but a closer examination showed a similar and ... : Published as part of Li, Yang, Boonprakob, Atchaneey, Gaonkar, Chetan C., Kooistra, Wiebe H. C. F., Lange, Carina B., Hernández-Becerril, David, Chen, Zuoyi, Moestrup, Øjvind & Lundholm, Nina, 2017, Diversity in the Globally Distributed Diatom Genus Chaetoceros (Bacillariophyceae): Three New Species from Warm-Temperate Waters, pp. 1-38 in PLoS ONE (e 0168887) (e 0168887) 12 (1) on pages 5-26, DOI: 10.1371/journal.pone.0168887, http://zenodo.org/record/12827437 ...